1990
DOI: 10.1111/j.1464-410x.1990.tb14870.x
|View full text |Cite
|
Sign up to set email alerts
|

Identifiable Factors in Post‐prostatectomy Haemorrhage: the Role of Aspirin

Abstract: Post-operative haemorrhagic complications following the ingestion of aspirin have been reported after several types of surgery, most notably coronary artery bypass surgery. In this study, aspirin ingestion also appeared to be a significant aetiological factor in post-prostatectomy haemorrhage. This is explained in terms of its inhibitory effect on platelet aggregation. A history of aspirin ingestion should be carefully sought and its haemorrhagic implications considered prior to prostatectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(45 citation statements)
references
References 16 publications
2
43
0
Order By: Relevance
“…Many previous studies have addressed the question of factors influencing TURP bleeding [3, 4, 5, 6, 7, 8, 9, 10]. Each study usually addressed a few factors (usually 2–5), and different studies used different methods of blood estimation, making comparison of studies or extrapolation of results difficult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many previous studies have addressed the question of factors influencing TURP bleeding [3, 4, 5, 6, 7, 8, 9, 10]. Each study usually addressed a few factors (usually 2–5), and different studies used different methods of blood estimation, making comparison of studies or extrapolation of results difficult.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, many of the so far studied factors are still controversial, being associated with bleeding in some studies and denied such association in others. Such factors include age of patient and mean blood pressure [8], operating time [5, 6], type of anaesthesia [4, 6], gland histology [6, 9]and many others. In this prospective study, we aim at finding out whether any of a set of predefined clinical and laboratory parameters correlate with blood loss caused by TURP.…”
Section: Introductionmentioning
confidence: 99%
“…4,20 Previously, a retrospective analysis of patients undergoing open radical retropubic prostatectomy in 1990 detected a higher risk for bleeding in 52 aspirin-treated patients. 21 Because of ambiguous data about the safety of transurethral resection of the prostate (conventional electroresection), the recommendations for prostate surgery do not provide definite advice. 10,22,23 Considering the reports on blood loss in non-OAT patients, laparoscopic radical prostatectomy and RARP seemed to be promising techniques for the reduction of hemorrhagic complications.…”
Section: Discussionmentioning
confidence: 99%
“…A similar low risk of bleeding in patients with low-dose aspirin medication was observed by Shiffmann et al [46] after endoscopic biopsy or polypectomy, and by Madan et al [30] who conducted a prospective study and performed minor oral surgery in 51 patients without stopping daily low-dose aspirin therapy. When focusing on more invasive operative procedures, like in the topic of prostatectomy [35,50,54] and cardiac surgery [3,8,9,14,20,33,44,45,53], aspirin is a recognized risk factor contributing to excessive peri-operative bleeding and the need for reoperation. Watson et al [54] identified aspirin ingestion, already in 1990, to be a significant etiological factor in post-prostatectomy hemorrhage, and Nielsen et al [35] approved the same statement in a prospective, randomized, double-blind, placebo-controlled study 10 years later.…”
Section: Comparable Surveysmentioning
confidence: 99%
“…When focusing on more invasive operative procedures, like in the topic of prostatectomy [35,50,54] and cardiac surgery [3,8,9,14,20,33,44,45,53], aspirin is a recognized risk factor contributing to excessive peri-operative bleeding and the need for reoperation. Watson et al [54] identified aspirin ingestion, already in 1990, to be a significant etiological factor in post-prostatectomy hemorrhage, and Nielsen et al [35] approved the same statement in a prospective, randomized, double-blind, placebo-controlled study 10 years later. They stated that although there was no significant difference in the median operative blood loss between patients receiving a transurethral prostatectomy either with or without pre-operative aspirin medication, the long-term low-dose ASA therapy is associated with a significant increase in the post-operative blood loss.…”
Section: Comparable Surveysmentioning
confidence: 99%